Outcome of laparoscopic sleeve gastrectomy for treatment morbidly obese patients in Srinagarind hospital - Punchai, Suriya; Wittayapairoj, Jakrapan; Paonariang, Krisada; Jenwithisuk, Kriangsak; Saeseaw, O-Tur; Udomsawaengsup, Suthep; Thanapiasal, Chaiyut (Asia-Pacific Journal of Science and Technology, 2016)
Background: Laparoscopic sleeve gastrectomy (LSG) has been increasingly popular procedure for treatment morbidly obese patients and showing good weight loss and resolution of comorbidity diseases. The objective of this study was to evaluate postoperative outcome in term of operative complication, weight loss and comorbidity improvement after laparoscopic sleeve gastrectomy. Methods: From July 2011 to December 2014 there is 70 patients (45 woman; 64 percent) with an average age of 37.7 years (range; 17-62 years), mean body weight was 126.5 kg (range; 83-250 kg), mean BMI was 45.7 kg/m2 (range; 33-77 kg/m2) who underwent laparoscopic sleeve gastrectomy for treatment morbid obesity. Postoperative time, 1st day postoperative pain, postoperative complication and postoperative follow up data for the body weight change, percent EWL, BMI and improvement of comorbidity at the 6th, 9th,12th, 18th, and 24th months were recorded. Results: The mean operative time was 75 minutes. The mean operative blood loss was 20 ml. The mean 1st day postoperative pain score was 4. No conversion to laparotomy had to be performed. The mean percentages of excessive body weight loss (EWL) were 46.78 percent at 6 months, 59.75 percent at 1 year, 64.53 percent at 18 months, and 62.92 percent at 2 years. The mean BMI were 35.57 kg/m2 at 6 months, 32.69 kg/m2 at 1 year, 29.23 kg/m2 at 18 months, and 29.45 kg/m2 at 2 years. The rate of resolution of OSA was 65.7 percent and improvement of OSA was 31.4 percent. The rate of resolution of hypertension was 68.9 percent and improvement of hypertension was 31.1 percent. The rate of resolution of DM was 70 percent and improvement of DM was 30 percent. The rate of postoperative complication was 4.2 percent. Conclusions: Laparoscopic sleeve gastrectomy is safe and effective procedure for treatment morbidly obese patients. However, weight regained need to evaluated in long term follow up.